PERLINDUNGAN SAHAM MINORITAS DALAM HOLDING COMPANY - AUDRYA LUVIKA SIREGAR; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
In any corporations, there are majority shareholders and minority shareholders. Minority shareholders are the parties who have stocks with very small amounts in the company. However, minority shareholders are still part of the company, which also has the rights over the company, therefore these minority shareholder's rights should be protected. The research that was used in compiling this thesis using normative legal research methods (methods of librarianship), that are examined by collecting and processing data from books, legislations, journals, websites and other scientific writing results that closely related to The Protection of Minority Shareholders in the Holding Company in Indonesia. The result of this thesis can be concluded that the rights of minority shareholders in the holding company must be protected, the protection can be reached through the Appraisal Right, which protect minority shareholders as a way out for them to leave the company that has changed fundamentally, if they does not consent to the change that referred to. Kata Kunci: Perseroan Terbatas, Holding Company, Pemegang Saham